A case report of sudden cardiac arrest and torsade de pointes induced by the second-generation tyrosine kinase inhibitor dasatinib combined with fluconazole - Yuan, Yuting; Wang, Chunjian; Yao, Hongying (Frontiers in Cardiovascular Medicine, 2023)
A-41-year-old man diagnosed with acute myeloid leukemia (AML) survivedccessfully lived through dasatinib+fluconazole drug-induced long QT syndrome, sudden cardiac death arrest, and torsade de pointes after acceptance of dasatinib combined with fluconazole. Drug features and drug interaction jointly contributedcatalyzed to the whole process. Therefore, appropriate attention to drug interaction and close ECG monitoring of ECG are highly recommended for hospitalized patients, especially for those undergoing treated with multi-drug regimens.